A cross-sectional study design to assess the sexual experiences and contraceptive use of adolescents and youths attending high school and college in Jimma town - Gudina Terefe Tucho; Netsanet Workneh; Mubarek Abera; Jemal Abafita (BMC, 2022)
Abstract Background Adolescents and youths in Ethiopia have limited access to reproductive health services designed to address their needs. Therefore, the study aims to assess adolescents' and youth's sexual practice, contraceptive use, and behavioral patterns towards safe sexual exercise. Methods A quantitative cross-sectional study design was used on 374 students selected from high school and vocational colleges to assess their sexual experience and contraceptive use and related perceptions using pre-tested self-administered semi-structured questionnaires. We used descriptive analyses to report their sexual and reproductive health status and logistic regression to examine the association between contraceptive use and other variables. Results The results show that 52.7% of the respondents (students) migrated or moved from rural to urban to continue their high school and college education at urban. 41.7% of the respondents were with less than 18 years, of which 75.9% of them already initiated sexual intercourse. Of all the students who started sexual intercourse (51.1%), only 30.9% used contraceptives, but condom use accounts for 49.2%. Overall, 84.8% of those who practiced sexual intercourse were at risk of acquiring sexually transmitted diseases due to not using a condom. About 3% of the respondents reported unwanted pregnancy experiences, of which 64% of these pregnancies were reported to be aborted. Conclusion Adolescents and youths attending high schools and College are at increased risk of acquiring HIV and unwanted pregnancy due to low levels of contraceptive use. Specifically, a designed youths-friendly reproductive health service is needed to avert related problems and contribute to sustainable development goals.